CALORIES CATERING, KATERING DENGAN FASILITAS PERHITUNGAN KEBUTUHAN KALORI, SARAGI (SARAPAN PAGI) DELIVERY DAN KONSULTASI NUTRISI SECARA GRATIS - Riyadi, D.; Fidayanti, Shinta P.; Pradanta, Yazid E. (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Malnutrition caused by lack of food supplies, lack of good environmental quality, and lack of public knowledge about nutrition. The prevalence of malnutrition status in adolescents aged 16-18 years is quite high based on data obtained from Riskesdas in 2010. The prevalence of short adolescents with percentage figures as much as 31.2 % and the prevalence of skinny teenager with a percentage figure of 8.9 %. While the prevalence of very lean by IMT according to the characteristics of the respondents, especially in South Kalimantan was ranked 2nd after the top of the 33 provinces of West Kalimantan in Indonesia. To solve the problem of malnutrition and with a pretty solid community activities, catering business into one of the right choices. Employers catering formally Banjarbaru in the region that has a large number of orders is only 3. The purpose of the application of Calories Catering business is making a business formation activity culinary creative, unique, and has advantages that no other catering business, which is a calculation facility needs calories, nutrition or health consultation, and delivery Saragi. In addition it helps assist the government in reducing the prevalence of malnutrition status and creating a quality human resources with the needs of calories according to consumer activity. Methods in the implementation of this effort is the preparation, marketing and service, return on capital, and sustainable profits in the business. During the 5 months of business activity passes successfully serve 19 spot orders, 1,278 boxes, with a turnover of Rp 14,926,500, -. Continuous effort is the primary focus of this effort.